Wind-fed Supermassive Black Hole Accretion by the Nuclear Star Cluster: The Case of M31* - Zhao Su; Zhiyuan Li; Zongnan Li (The Astrophysical Journal)
The central supermassive black hole (SMBH) of the Andromeda galaxy, known as M31*, exhibits dim electromagnetic emission and is inferred to have an extremely low accretion rate for its remarkable mass (∼10 ^8 M _⊙ ). In this work, we use three-dimensional hydrodynamical simulations to explore a previously untested scenario, in which M31* is fed by the collective stellar mass loss from its surrounding nuclear star cluster, manifested as a famous eccentric disk of predominantly old stellar populations. The stellar mass loss is assumed to be dominated by the slow and cold winds from 100 asymptotic giant-branch stars, which follow well-constrained Keplerian orbits around M31* and together provide a mass injection rate of ∼4 × 10 ^−5 M _⊙ yr ^−1 . The simulations achieve a quasi-steady state on a megayear timescale, at which point a quasi-Keplerian, cool ( T ∼ 10 ^3 –10 ^4 K) gas disk extending several parsecs is established. This disk is continuously supplied by the stellar winds and itself feeds the central SMBH. At the end of the simulations at 2 Myr, an accretion rate of ∼2 × 10 ^−5 M _⊙ yr ^−1 is found but could vary by a factor of a few depending on whether the subdominant gravity of the NSC or a moderate global inflow is included. The predicted X-ray luminosity of ∼10 ^36 erg s ^−1 , dominated by the hot ( T ∼ 10 ^7 –10 ^8 K) plasma within 0.2 pc of the SMBH, is consistent with Chandra observations. We conclude that the feeding mechanism of M31* is successfully identified, which has important implications for the working of dormant SMBHs prevalent in the local Universe.